Numerical analysis of the biomechanical complications accompanying the total hip replacement with NANOS-Prosthetic: bone remodelling and prosthesis migration - Almohallami A.; Behrens B.-A.; Bouguecha A.; Lerch M.; Betancur S.; Stukenborg-Colsman C.; Nolte I.; Lucas K. (Current Directions in Biomedical Engineering, 2015)
Aseptic loosening of the prosthesis is still a problem in artificial joint implants. The ýloosening can be caused by the resorption of the bone surrounding ýthe prosthesis according to stress shielding. A numerical model was developed and validated by means of DEXA-studies in order to ýanalyse the bone remodelling process in the periprosthetic bone. A total loss of about 3.7% of the bone density in the periprosthetic Femur with NANOS is computed. The bone remodelling calculation was validated by means of a DEXA-study with a 3-years-follow-up. The model was further developed in order to be able to calculate and consider the migration of the implants. This method was applied on the ýNANOS-implant with a computed total migration of about 0.43 mm. These calculations showed good results in comparison with a 2-year-follow-up clinical study, whereby a RSA-method was used to determine the stem migration in the bone. In order to ýstudy the mutual influence between the implant migration and the hip contact forces ý, a software is developed by our scientific group to couple a multi body simulation (MBS) of human lower limps with the FEA of the periprosthetic Femur.